Enhanced removal of methylene blue dye in aqueous solution using eco-friendly Fe(III)–montmorillonite. (2017) - Vinuth, M.; Naik, H.S. Bhojya; Vinoda, B.M.; Gururaj, H.; Thomas, N.; Arunkumar, G.
Abstract: We have explored the highly efficient and environmentally benign clay mineral, Fe(III)–montmorillonite (Fe(III)–Mt), for methylene blue (MB) dye removal in aqueous solution. The Fe(III)–Mt was interacted with MB dye solution at different pH, temperature and solid-to-liquid ratio. The concentration of MB dye removal was estimated from its optical density at λmax = 665 nm using UV-Vis spectrophotometer. The MB dye molecules removal was rapid at basic pH and increases with temperature up to 40 °C. A complete reduction (100%) was occurred in about 7 min at pH 7 & 10 while at pH 3 in about 10 min. The time taken for complete reduction at 0 °C, RT (30 °C), and 40 °C are 10, 7 and 5 min respectively. The removalfollowed by adsorption of dye molecules on the spent clay mineral was evident from FESEM/EDX analysis. More importantly, Fe(III)–Mt could be separated and retrieved easily after the reaction by centrifugation from the degraded MB dye solution. This study reveals that Fe(III)–Mt has the potential to be used as reductant/adsorbent to remove cationic dye molecules effectively and rapidly from drinking water and large scale of industrial wastewater.